Alien fish in Neotropical reservoirs: Assessing multiple hypotheses in invasion biology. (February 2021) - Muniz, Carolina M.; García-Berthou, Emili; Ganassin, Maria Julia M.; Agostinho, Angelo A.; Gomes, Luiz C.
Highlights: We analyzed the relative importance of some invasion hypotheses. There was evidence for biotic acceptance in reservoirs. More productive reservoirs are more susceptible to invasion. Alien fishes respond to limnological variation in a similar way than native species. Practical implications are provided to prioritize management interventions. Abstract: Invasive alien species are one of the main components of global ecological change, the second known cause of animal extinctions, and very costly in terms of ecosystem services. Invasive alien species and damming are two of the most impacting alterations in freshwater ecosystems, and understanding the processes that govern biological invasions in these habitats is of enormous conceptual and practical importance. About 39 competing and overlapping hypotheses have been proposed in invasion biology that have been recently grouped in four (or five) concept clusters, namely the: propagule, resource availability, biotic interaction and Darwin's clusters. We analyzed the relative importance of three of these concept clusters in Neotropical fish assemblages, using data from 29 reservoirs and variation partitioning analyses. We show that alien fish assemblages respond to variation in limnological characteristics in a way similar than native species, usually with positive effects of increased temperature, conductivity and chlorophyll- a concentration and decreasing turbidity. Overall, we found support for some hypotheses included in resource availability and Darwin's clusters, such as increased resource availability and biotic acceptance, and no evidence of strong biotic resistance, marked effects of human disturbance, as measured by land-use changes, or propagule/colonization pressures. We discuss the potential reasons and management implications of these findings. Our study illustrates that analyzing the importance of classical hypotheses of invasion biology in tropical freshwaters and other ecosystems enhances ecological understanding and provides practical implications to prioritize management interventions and mitigate ecological impacts.